(untitled) (Journal of the Bangladesh Agricultural University, 2018)
Integrated farming system modifies the commercial farming system which ensures higher food production to equate the demand, environmental protection through effective recycling of waste and increased farm income. The present study was undertaken to examine the relative profitability of FSRD project farmers and non-project farmers of integrated farming system. Eighty (80) farmers (40 from FSRD project and 40 from non-project farmers) were selected from Kalihati Upazila under Tangail district of Bangladesh. In the study area, vegetables, fish and poultry enterprises were integrated under technological intervention. The waste of poultry farm was used in fish production and the soil of the pond was used in vegetables cultivation. Per hectare net returns from integrated farming were estimated at Tk513458.10 and Tk256511.90for FSRD project farmers and non-project farmers, respectively. Benefit cost ratio (BCR) was 1.66 for FSRD project farmers and1.37 for non-project farmers. In functional analysis, human labor, fingerling, feed, fertilizer, insecticides costs in case of FSRD project farmers and human labor, feed, salt and lime costs in case of non-project farmers had significant impact on per hectare return of integrated farming. FSRD project farmers were more profitable than the non-project farmers. Therefore, it can be concluded that there is great scope to improve the overall economic condition of farmers through introducing integrated farming system in Tangail District of Bangladesh. J. Bangladesh Agril. Univ. 16(1): 117-122, April 2018